Microstructure and mechanical properties of an additively manufactured AlSi10Mg based alloy - YAYLA, PAŞA (My University, 2023)
In this study, the mechanical properties, fractography, and microstructure relationship of AlSi10Mg produced by laser powder bed fusion were established. Laser powder bed fusion is an additive manufacturing method that is an innovative technique. Since additive manufacturing is a new technique, utilizing materials requires studies investigating mechanical properties, fractography, and microstructure. This is vital because these characteristics are used before choosing the materials to manufacture the desired parts. The tensile, the Charpy impact, the hardness, and the density tests were applied to identify the mechanical properties of AlSi10Mg specimens. After that, the fractographic features and microstructure of the material were observed via an optical microscope and a scanning electron microscope. Finally, these results were related to each other. The results of tensile, the Charpy impact and fractography revealed that the laser powder bed additively manufactured AlSi10Mg alloy exhibited ductile-brittle type failure behaviour. As-built additively manufactured AlSi10Mg demonstrated higher yield strength, ultimate tensile strength, and microhardness but less density than as-built cast-produced AlSi10Mg.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, KARAKTERİZASYON VE TEST; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, CHARACTERIZATION & TESTING; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; additive manufacturing; AlSi10Mg alloy; fractography; mechanical properties; microstructure